Providing chicks with extra food lowers male but not female provisioning in the House Sparrow Passer domesticus. (17th July 2013) - Cleasby, Ian R.; Nakagawa, Shinichi; Burke, Terry
Abstract : We assessed whether adult House Sparrows Passer domesticus adjusted their provisioning in response to an experimental increase in the nutritional condition of their nestlings. When we supplemented chicks directly with additional food, male parents, but not female parents, reduced their provisioning. The results for males, but not females, run contrary to a previous experiment in this species. In addition, female provisioning was positively associated with both brood size and the age of the brood. In contrast, whereas male provisioning was positively associated with brood size, males did not increase provisioning as their chicks grew older. Males, but not females, exhibited repeatability in their provisioning. Food supplementation had a larger positive effect upon nestling survival in smaller broods than in larger broods. Overall, there appear to be fundamental differences between males and females in how decisions regarding the level of parental investment in the current brood are made.